2017
DOI: 10.3389/fpls.2017.01184
|View full text |Cite
|
Sign up to set email alerts
|

BdCIPK31, a Calcineurin B-Like Protein-Interacting Protein Kinase, Regulates Plant Response to Drought and Salt Stress

Abstract: Calcineurin B-like protein interacting protein kinases (CIPKs) are vital elements in plant abiotic stress signaling pathways. However, the functional mechanism of CIPKs has not been understood clearly, especially in Brachypodium distachyon, a new monocot model plant. In this study, BdCIPK31, a CIPK gene from B. distachyon was characterized. BdCIPK31 was downregulated by polyethylene glycol, NaCl, H2O2, and abscisic acid (ABA) treatments. Transgenic tobacco plants overexpressing BdCIPK31 presented improved drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 82 publications
1
32
0
Order By: Relevance
“…Overexpressing BdCIPK31 functions in stomatal closure, ion homeostasis, ROS scavenging, osmolyte biosynthesis, and transcriptional regulation of stress-related genes. In fact, it appears that transgenic tobacco plants overexpressing BdCIPK31 presented improved drought and salt tolerance and displayed hypersensitive response to exogenous ABA [196]. Further investigations revealed that BdCIPK31 functioned positively in ABA-mediated stomatal closure, and transgenic tobacco exhibited reduced water loss under dehydration conditions compared with the controls.…”
Section: Physiological Roles Of Cbls and Cipks In Plant Responses To mentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpressing BdCIPK31 functions in stomatal closure, ion homeostasis, ROS scavenging, osmolyte biosynthesis, and transcriptional regulation of stress-related genes. In fact, it appears that transgenic tobacco plants overexpressing BdCIPK31 presented improved drought and salt tolerance and displayed hypersensitive response to exogenous ABA [196]. Further investigations revealed that BdCIPK31 functioned positively in ABA-mediated stomatal closure, and transgenic tobacco exhibited reduced water loss under dehydration conditions compared with the controls.…”
Section: Physiological Roles Of Cbls and Cipks In Plant Responses To mentioning
confidence: 99%
“…In 2017, it was reported that BdCIPK31, a CIPK gene from Brachypodium distachyon, functions positively to drought and salt stress through the ABA signaling pathway [196]. Overexpressing BdCIPK31 functions in stomatal closure, ion homeostasis, ROS scavenging, osmolyte biosynthesis, and transcriptional regulation of stress-related genes.…”
Section: Physiological Roles Of Cbls and Cipks In Plant Responses To mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Interestingly, like CBL4-CIPK24 in Arabidopsis, many other members (CBL1, CBL9, PsCBL, CIPK1, CIPK2, CIPK25, CIPK26 and CIPK31) are also involved in the network-like signaling system to mediate response to salt stress, including ABA-dependent signaling cascades. 16,17,18,19,20,21,22 However, although important progress has been achieved in understanding the downstream targets and physiological functions of some of these proteins, many queries remain to be explored.…”
mentioning
confidence: 99%
“…Soil salinization, which affects up to 7% of arable land worldwide, is one of the major in uencing factors which has severely limited crop growth and grain yield production due to the sensitivity of crops to high concentrations of salt [1,2]. A high salt concentration could affect plants by increasing osmotic stress and ionic toxicity, which destroyed many plant physiology and metabolic processes, includingleaf photosynthesis, chloroplast electron-transfer, integrity of cell membrane and even the protein synthesis, and to several morphological changes, which reduce crop grain yield production [3,4]. Furthermore, longterm groundwater irrigation also salinizes the soil of inland farmland [5].…”
Section: Introductionmentioning
confidence: 99%